KEMAMPUAN BERBICARA DITINJAU DARI SUKU DAN BAHASA IBU PADA SISWA KELAS IV SDN 007 SUKADAMAI KECAMATAN SINGINGI HILIR - Windi Khairunnisa; Febrina Dafit (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to describe the Indonesian speaking ability of fourth-grade students at SDN 007 Sukadamai, Singingi Hilir District, viewed from their ethnicity and mother tongue. This research employed a qualitative descriptive approach. The subjects consisted of 32 fourth-grade students, while six students representing good, fair, and poor speaking ability categories and one classroom teacher were selected as research informants. Data were collected through speaking tests, questionnaires, interviews, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing. The findings showed that students' Indonesian speaking ability varied across three categories: good, fair, and poor. Students from the same ethnic background demonstrated different levels of speaking ability, indicating that ethnicity did not directly determine speaking ability. Likewise, students whose mother tongue was Indonesian tended to communicate more fluently in Indonesian. However, students whose mother tongue was a regional language were also able to demonstrate good speaking ability when they frequently used Indonesian in daily communication. Therefore, Indonesian speaking ability is influenced not only by ethnicity and mother tongue but also by language environment, communication habits, opportunities to practice speaking, and students' self-confidence.